Analysis of the D1S80 VNTR locus polymorphism in the Nubian population - Ahmed, Soha Rabie (AUC Knowledge Fountain, 2016)
D1S80 (1p35-p36), variable Number of tandem repeat (VNTR,) is a minisatellite molecular genetic marker. It is known by its high polymorphism that makes it a powerful marker in the forensic applications, paternity testing, and evolutionary studies. Hypervariable D1S80 locus has been applied to study the genetic structure of the Nubian population in Southern Egypt. PCR has been applied for repeats amplification and analyzed on 2% agarose gel. 75 genotypes and 36 alleles with their frequencies were detected for 105 unrelated individuals. Allele 27 has the highest frequency 0.119% followed by allele 26 with frequency 0.09%. Heterozygosity was calculated as 0.69%. P values of Chi2 and exact tests indicate departure from Hardy-Weinberg equilibrium which points to the inbreeding within the population. Non-metric dimensional scaling and hierarchical cluster dedrograms were applied to determine the phylogenetic relationship between the Nubian population and other worldwide populations. Both plots indicated the proximity of the Nubian population to Modern Malay population as a result of dominance of 27 alleles in both populations.